How do you solve the equation x^2 + 2x + 3 = 0?

To solve the quadratic equation x² + 2x + 3 = 0, we can use the quadratic formula, which is given by:

x = (-b ± √(b² – 4ac)) / 2a

Here, a = 1, b = 2, and c = 3. First, we need to calculate the discriminant, b² – 4ac:

– Calculate : 2² = 4
– Calculate 4ac: 4 * 1 * 3 = 12

– Now, compute the discriminant: 4 – 12 = -8

Since the discriminant is negative, this means that the equation has no real solutions. However, we can find the complex solutions.

Now, substituting the values into the quadratic formula:

x = (-2 ± √(-8)) / 2(1)

We can simplify this further:

x = (-2 ± 2i√2) / 2

Breaking this down:

x = -1 ± i√2

Thus, the solutions to the equation x² + 2x + 3 = 0 are:

x = -1 + i√2 and x = -1 – i√2

More Related Questions